Persepsi Mahasiswa Tentang Pertukaran Mahasiswa program Global Citizenship Exchange - Fitriasari, Susan; Insani, Nisrina Nurul; Fauziah, Syifa; Liah, Asyifa Nurul (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Higher education must immediately adapt because the Industrial Revolution 4.0 is changing social life and the order of society. Higher education plays an important role in developing students who are ready to face this shift. The Pancasila and Citizenship Education study program at FPIPS UPI plays a significant role through the innovative Global Citizenship Exchange Program. Through international exchange, this program aims to enhance students' abilities as global citizens. This case study uses qualitative methodology to collect data through interviews, questionnaires and documentation. The results show students' high interest and interest in this program, and the results show that global citizenship skills increase. Initiatives like these are critical to preparing students for future changes and ensuring that they contribute positively to an increasingly connected global society.